Diastereoselective Synthesis of P‐Chirogenic and Atropisomeric 2, 2′‐Bisphosphino‐1, 1′‐binaphthyls Enabled by Internal Phosphine Oxide Directing Groups. (16th April 2020) - Xue, Qingquan; Huo, Shangfei; Wang, Tingyi; Wang, Zeming; Li, Jianli; Zhu, Meifang; Zuo, Weiwei
Abstract: Diphosphine ligands that merge both axial and P‐centered chirality may exhibit superior or unique properties. Herein we report the diastereoselective introduction of P‐centered chirality at the 2‐position of the axially chiral 2′‐(phosphine oxide)‐1, 1′‐binaphthyl scaffold. A lithium–bromide exchange reaction of a 2‐bromo‐2′‐(phosphine oxide)‐1, 1′‐binaphthyl and treatment with dichlorophosphines followed by a nucleophilic organometallic reagent afforded unsymmetrical 2‐phosphino‐2′‐(phosphine oxide)‐1, 1′‐binaphthyls with binaphthyl axial chirality and one or two phosphorus stereocenters with a variety of P substituents. The final diastereomerically pure 2, 2′‐bisphosphino‐1, 1′‐binaphthyls were obtained by reduction of the phosphine oxide directing group. Preliminary results demonstrated that a ligand with this hybrid chirality could induce higher stereoselectivity in the metal‐complex‐catalyzed asymmetric hydrogenation of a dialkyl ketone. Abstract : Chiral in more ways than one : Atropisomeric and P‐chirogenic 2, 2′‐bisphosphino‐1, 1′‐binaphthyls with configurationally controllable phosphorus centers were synthesized with excellent diastereoselectivity by the use of a 2′‐phosphine oxide directing group and its regio‐ and stereospecific reduction (see scheme). Preliminary results suggested that such hybrid chirality was beneficial in the metal‐complex‐catalyzed asymmetric hydrogenation of a dialkyl ketone.